Profiling Antibody Response Patterns in COVID-19: Spike S1-Reactive IgA Signature in the Evolution of SARS-CoV-2 Infection - Siracusano, Gabriel; Brombin, Chiara; Pastori, Claudia; Cugnata, Federica; Noviello, Maddalena; Tassi, Elena; Princi, Denise; Cantoni, Diego; Malnati, Mauro S.; Maugeri, Norma; Bozzi, Carla; Saretto, Gianni; et al. (Frontiers in Immunology, 2021)
This contribution explores in a new statistical perspective the antibody responses to SARS-CoV-2 in 141 COVID-19 patients exhibiting a broad range of clinical manifestations. This cohort accurately reflects the characteristics of the first wave of the SARS-CoV-2 pandemic in Italy. We determined the IgM, IgA and IgG levels towards SARS-CoV-2 S1, S2, and NP antigens, evaluating their neutralizing activity and relationship with clinical signatures. Moreover, we longitudinally followed 72 patients up to 9 months post symptoms onset to study the persistence of antibodies levels. Our results showed that the majority of COVID-19 patients developed an early virus-specific antibody response. The magnitude and the neutralizing properties of the response were heterogeneous regardless the severity of the disease. Antibody levels dropped over time, even though spike reactive IgG and IgA were still detectable up to 9 months. Early baseline antibody levels were key drivers of the subsequent antibody production and the long-lasting protection against SARS-CoV-2. Importantly, we identified anti-S1 IgA as a good surrogate marker to predict the clinical course of COVID-19. Characterizing the antibody response after SARS−CoV−2 infection is relevant for the early clinical management of patients as soon as they are diagnosed and for implementing the current vaccination strategies.